The Optimization of Peer Assessment in the Education Curriculum of Health Workers: A Scoping Review - Nurfitriyani, Ela; Indra Susanti, Ari; Susiarno, Hadi; Septiana, Krisna Siska (JTP - Jurnal Teknologi Pendidikan, 2024)
Peer Assessment has the advantage of providing effective feedback, improving social interaction between individuals, and improving the overall quality of learning. This research was conducted to explore scientific evidence regarding the benefits and challenges of peer assessment implementation, as well as to understand its impact on professional competence and learning quality. This research will help optimize the use of peer assessment in the education curriculum of health workers. This study aims to analyze the effectiveness of peer assessment in learning the health education curriculum. This study uses the scoping review research method to analyze various research sources related to the same topic. The research question is based on mnemonic Population, Exposure, and Outcome (PEO). The results of the article review were obtained from the synthesis of three main ones: the benefits of peer assessment, the implementation of peer assessment, and the impact of peer assessment. The articles are from various developed countries (United Kingdom, Singapore, Netherlands, and Belgium) as well as developing countries such as (Indonesia, and Turkey). Peer assessment in the midwifery curriculum has been proven to significantly improve the quality of learning and student competence. In addition, the use of peer assessment facilitates interactive and in-depth learning, so that students are actively involved in the evaluation process in the form of feedback to improve clinical and interpersonal skills.